Magneto-thermoelastic excitation induced by a thermal shock: a study under the purview of three phase lag theory - Tiwari R.; Misra J.C. (My University, 2025)
The present work is devoted to the study of the propagation of magneto-thermoelastic waves generated by a thermal shock in a finitely conducting elastic half-space. Three phase lag (TPL) theory of thermoelasticity has been applied to account for the interaction among the elastic, thermal and magnetic fields. Mechanical load and thermal shock has been applied on the boundary of the medium. Laplace transform technique on time has been used to obtain the solutions. By considering an illustrative example, numerical results have been computed to explore the physics of the problem. The results for the TPL model have been compared with those for the dual phase lag theory. The study reveals that the distribution of temperature, displacement and stress for the TPL model are significantly different from those of the two phase lag models, as the time progresses until the steady state is reached. © 2020 Informa UK Limited, trading as Taylor & Francis Group.